A bibliometric review of technopreneurship: intellectual structure, key themes, and research frontiers - Rumangkit, Stefanus; Hadi, Antonius Satria; Osman, Muhamad Zulkiflee (Indonesia Research and Study Center, 2025)
The rapid advancement of digital technologies has positioned technopreneurship as a key paradigm in modern entrepreneurship research. Unlike traditional entrepreneurship, technopreneurship integrates technological expertise with business vision to foster innovation, competitiveness, and sustainable growth. This study conducts a bibliometric review of technopreneurship literature in Scopus-indexed journals (2020–2025) within Business, Management, and Accounting. Using VOSviewer and Bibliometrix, the analysis covers publication productivity, citation impact, collaboration networks, thematic clusters, and research frontiers. Findings show Indonesia as the most productive country, driven by its dynamic startup ecosystem and academic focus. Key themes highlight business incubators, digital platforms, and green innovation. Eleven clusters are identified, spanning AI in education, digital transformation, sustainability, and Education 4.0. Emerging frontiers include technopreneurial self-efficacy, engineering education, economic growth, and disruptive technologies, offering theoretical and practical insights for stakeholders.